Campur Kode dan Alih Kode (Analisis Pada Konten Instagram Sehand Azhar) - Zulli Umri Siregar; Fathur Riyadhi Arsal; Khairun Nisa Hasugian; Nabila Mutia Tsani (Hijai - Journal on Arabic Language and Literature, 2025)
This study aims to examine the use of code switching and code mixing in Instagram content by Sehand Azhar, especially in the form of video reels, to understand its function and meaning in digital communication. The method used is a descriptive qualitative case study with the technique of simak libat cakap. Data were taken from 15 video reels watched by more than 20,000 people, and analyzed using a summative approach to identify elements of code-switching and code-mixing. The results show that the use of code-switching and code-mixing in Azhar's content enriches expression and strengthens social identity between speakers, with some Arabic elements that are difficult to translate into Indonesian, thus adding aesthetic and functional value in the pesantren context. The analysis also reveals that this phenomenon is supported by the multilingual ability of the speakers and the appeal of Arabic among the audience, most of whom have a pesantren background. The implications of this study show that code-switching and code-mixing in social media not only strengthen social relations, but also contribute to the preservation of pesantren language and culture, and open up opportunities for further research on the impact of multilingualism in digital communication. Keywords: Code Switch, Code Mix, Instagram